ANALYSIS OF POTENTIAL CONTAMINANT TRANSPORT BY USING GROUNDWATER MODELING IN UNDERGROUND COAL GASIFICATION (UCG) PROJECT - Luthfi Luthansyah, Muhamad
In UCG operation all reaction products of the waste are transported to the surface for treatment. In addition, because the pressure of the UCG cavity is lower than the hydrostatic pressure of groundwater (groundwater surrounding the cavity flows into the UCG cavity), there is a mechanism of flushing pollutants by groundwater. The pollutants that are flushed out by the groundwater are then transported with the UCG products to the surface, although there is still the potential for some waste to remain in the UCG cavity, so that the cavity has the potential to become a source of contaminants, especially to groundwater, such as: Phenol, BTEX (Benzene, Toluene, Ethyl Benzene, and Xylenes) and PAH (Polycyclic Aromatic Hydrocarbon). Contaminant transport analysis was carried out to see the potential spread of contaminants from the gasification area to surrounding locations. Primarily towards the potential spread of contaminants towards shallow aquifers or sand layers above the mudstone flanking layer. Contaminant transport simulations were carried out with the help of modflow software using the USGS SEAWAT flow engine and assigning sorption parameters with the Langmuir isotherm equation (equilibrium-controlled).